Glioblastoma in the Elderly: The Impact of Advanced Age on Treatment and Survival - Mariniello, Giuseppe; Peca, Carmela; De Caro, Marialaura Del Basso; Giamundo, Arcangelo; Donzelli, Renato; Maiuri, Francesco (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Objective To evaluate the effects of combined treatments on the outcome and survival of elderly (≥ 65 years) patients with glioblastoma as compared with younger ones.Material and Methods Fifty consecutive elderly (≥ 65 years) patients (group A) who underwent complete or subtotal (> 80%) resection of brain glioblastoma followed by irradiation and chemotherapy with temozolomide between 2004 and 2009 were retrospectively reviewed and compared with 50 glioblastoma patients aged < 65 years, treated in the same period (group B). Patient sex, tumor location, size and side, combined treatments, reoperation, progression-free survival, and overall survival were compared in the two groups by using the Kaplan-Meyer method.Results There were no significant differences between the two groups for tumor location, size and side, and Ki-67 Li. Forty-four of 50 group B patients were treated by the Stupp protocol, whereas all group A patients underwent irradiation and adjuvant temozolomide. Second-line chemotherapy was administrated in 32% of group A and 76% of group B cases, and reoperation was performed in 16% and 36%, respectively. The median survival of the overall series of 100 patients was 15.6 months. Group A patients (≥ 65 years) had a median survival of 14.5 months, significantly lower than group B cases (17 months) (p = 0.02).Conclusion Elderly patients with glioblastoma may benefit from combined treatments, including surgery, radiotherapy, and chemotherapy. Although younger patients do survive longer than older ones, the difference of survival is less significant if several criteria of selection to surgery, such as good Karnofsky performance status (KPS), largely resectable tumor, and no significant comorbidity, are respected.
Keywords: glioblastoma; age; elderly; surgery